Development of Terrain Analysis Database Using Military Geographic Information System - Mohamad Rabab, Mohd Zambri (2002)
The Information and Communication Technology (ICT) that includes military geospatial information will play a key role in the Revolution of Military Affair (RMA) for future warfare. The Terrain Analysis (TA) database is one of the military geospatial information that needs to be established in the Malaysian Armed Forces (MAF) in order to enable various Military Geographic Information System (MGIS) to perform analyses and produce Tactical Decision Aids (TDA) products. This study focused on the establishment of TA database structure that consisted of several layers namely Surface Configuration - Slope, Vegetation, Surface Material - Soils, Surface Drainage, Transportation and Obstacle Layers. A prototype T A database was established in order to evaluate the effectiveness of the database in generating Cross Country Movement (CCM) map. Results revealed that the topographic data from Department of Survey and Mapping Malaysia in Topologized Topographic Mapping (TTM) database, soil data from Department of Agriculture and the analyses of IKONOS imagery and ground data collection using GPS Geo Explorer 3 have contributed significantly to the development of prototype TA database. GIS technology was thoroughly utilized in implementing a user interface menu and CCM map from prototype TA database. Results showed that GIS technology has provided a powerful tool in successfully generating both products.